Physicians' opinions about partner notification methods: case reporting, patient referral, and provider referral. (30th January 2004) - Hogben, M; St Lawrence, J S; Montaño, D E; Kasprzyk, D; Leichliter, J S; Phillips, W R
Abstract : Background: The United States has relied upon partner notification strategies to help break the chain of infection and re-infection for sexually transmitted diseases (STD). Physicians are a vital link in the system of STD control, but little is known of physician opinions about partner notification strategies. Methods: We collected opinions about partner notification from a national probability sample of physicians in specialties diagnosing STDs. Physicians responded to 17 questions about three relevant forms of STD partner notification: patient based referral, provider based referral, and case reporting. Results: Exploratory factor analyses showed that responses for each form of partner notification could be grouped into four categories: perceived practice norms, infection control, patient relationships, and time/money. Multivariate analyses of the factors showed that physicians endorsed patient based referral most favourably and provider based referral least favourably. Conclusion: Physicians' opinions about partner notification strategies appear to reflect objective reality in some areas, but not in others. Strategies that improve the fit between physicians' opinions and effective notification are needed: some are discussed here.